2021
DOI: 10.1126/sciadv.abf1002
|View full text |Cite
|
Sign up to set email alerts
|

A highly conserved 3 10 helix within the kinesin motor domain is critical for kinesin function and human health

Abstract: KIF1A is a critical cargo transport motor within neurons. More than 100 known mutations result in KIF1A-associated neurological disorder (KAND), a degenerative condition for which there is no cure. A missense mutation, P305L, was identified in children diagnosed with KAND, but the molecular basis for the disease is unknown. We find that this conserved residue is part of an unusual 310 helix immediately adjacent to the family-specific K-loop, which facilitates a high microtubule-association rate. We find that t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
33
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 65 publications
5
33
0
Order By: Relevance
“…Most KIF1C stalls last several 100 ms, while only 20% of hyperactive KIF1A stalls exceed 50 ms. 17 While KIF1C has a 3.5-fold increased probability of backward slipping under load compared with KHC, constitutively active KIF1A shows 50-fold enhanced slipping. 17 , 23 Thus, our data suggest that KIF1C has unique force-generating properties that are intermediate between KIF1A and kinesin-1. These intermediate properties might enable KIF1C to be both highly processive 10 and generate substantial forces at low motor numbers, which might explain why KIF1C has been identified as the most effective cellular cargo transporter.…”
Section: Resultsmentioning
confidence: 68%
See 2 more Smart Citations
“…Most KIF1C stalls last several 100 ms, while only 20% of hyperactive KIF1A stalls exceed 50 ms. 17 While KIF1C has a 3.5-fold increased probability of backward slipping under load compared with KHC, constitutively active KIF1A shows 50-fold enhanced slipping. 17 , 23 Thus, our data suggest that KIF1C has unique force-generating properties that are intermediate between KIF1A and kinesin-1. These intermediate properties might enable KIF1C to be both highly processive 10 and generate substantial forces at low motor numbers, which might explain why KIF1C has been identified as the most effective cellular cargo transporter.…”
Section: Resultsmentioning
confidence: 68%
“…However, we found that the unloaded velocity of the motors was not negatively affected and even slightly increased, while mutations across the microtubule-binding interface of KIF1A resulted in lower single-molecule velocities. 23 , 26 , 30 Alanine scanning mutagenesis in kinesin-1 also identified two mutations (E220A and L317A) with a slightly higher velocity but reduced microtubule affinity. 31 Thus, the different outcome of reducing microtubule affinity on unloaded speed across kinesin-3 motors could be due to the biophysical properties of KIF1C being intermediate between kinesin-1 and KIF1A.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…In addition, the CAP-Gly domain mediates higher landing rates and an approximately 3-fold longer run length on tyrosinated versus detyrosinated MTs. Given that defects in kinesin-3's interactions with microtubules underly human neurodevelopmental and neurodegenerative diseases 64,65 , our results provide new insights into the various strategies adopted by kinesin-3 motors to augment the ability of the motor domains to move processively along microtubules to support cellular trafficking homeostasis and human health.…”
Section: Discussionmentioning
confidence: 89%
“…We also examined the processive kinesin-3 family member, KIF1A, which is known to transport cargo within neurons. Regulation of KIF1A transport within neurons is critical for human health as evidenced by a large cohort of human mutations in KIF1A that result in the neurodegenerative disorder KIF1A-associated neurological disease (KAND) (Boyle et al, 2021;Budaitis et al, 2021;Chiba et al, 2019;Lam et al, 2021). KIF1A has also been reported to be sensitive to the nucleotide state, and by extension possibly the dimer compaction state, of the microtubule lattice on which it travels (Guedes-Dias et al, 2019).…”
Section: Map Cooperativity Results In Differential Regulation Of Motor Proteinsmentioning
confidence: 99%